Blood-borne sphingosine 1-phosphate maintains vascular resistance, blood pressure, and cardiac function in mice - Ilaria Del Gaudio; Philippe Bonnin; Emilie Vessiéres; Estelle Robidel; Manuela C. Garcia; Coralyne Proux; Alexandre Boutigny; Véronique Baudrie; Hoa T. T. Ha; Ludovic Couty; Sandrine Placier; Ivo Cornelissen; et al. (Proceedings of the National Academy of Sciences, 2026)
Sphingosine 1-phosphate (S1P) is a bioactive lipid that circulates in plasma bound to high-density lipoproteins (HDL) and albumin. Circulating S1P levels correlate positively with systolic blood pressure (BP) in hypertension and negatively with severity in septic shock and with left ventricular function in heart disease. In mice, isolated deficiency in HDL-S1P and endothelial cell S1P receptor (R)-1 both trigger hypertension, supporting an essential role for HDL-S1P in endothelial function. Physiological roles of albumin-S1P and myocyte S1PRs in the cardiovascular system remain incompletely defined. We report that mice lacking all circulating S1P pools display hypotension and lack of BP increase with age, which contrasts with HDL-S1P deficiency and suggests an essential role for albumin-S1P in cardiovascular homeostasis. Although cardiac output was preserved in a basal state, left ventricular systolic function and contractile reserve were reduced in the absence of circulating S1P. Cardiac function and BP were partially or fully normalized by transfusion of erythrocytes capable of S1P production. Hypotension was accompanied by reduced peripheral resistance, and albumin-S1P, but not S1P complexed to an HDL-like chaperone, dose-dependently increased vascular resistance in isolated perfused kidneys via S1PR3 and S1PR2. Epistatic analysis supported a critical role for S1PR3 in S1P-dependent BP maintenance and pointed to a distinct origin of the cardiac phenotype. We thus uncover an essential role for circulating S1P in maintaining BP and left ventricular systolic function in mice. Our results also highlight distinct functions for the pools of S1P bound to HDL and to albumin, carrying both diagnostic and therapeutic implications.